The developmental and professional activities of female international soccer players from five high-performing nations. Issue 11 (17th June 2020) - Ford, Paul R.; Hodges, Nicola J.; Broadbent, David; O'Connor, Donna; Scott, Dawn; Datson, Naomi; Andersson, Helena A.; Williams, A. Mark
ABSTRACT: We study the developmental and professional activities engaged in by 86 female adult soccer players from the senior national teams of Australia, Canada, England, Sweden, and the United States of America. Players completed the Participation History Questionnaire (PHQ) to elicit the amount and type of activities engaged in across their developmental and professional years, including milestones, soccer-specific activity and engagement in other sport activity. Greater specialisation than diversification characterised their childhood developmental activities, including all players starting in soccer in childhood and accumulating more hours in soccer activity than other sports during this period. However, interindividual variation further characterised these childhood activities, with a proportion of players diversifying into other sports and/or soccer play to a greater or lesser degree during childhood when compared to the other players. The amount of coach-led soccer practice increased for all players across their development culminating in an average of 15–16 h/wk across a 40-week season in early adulthood. In contrast, the amount of engagement in other sports and soccer peer-led play varied between players but generally decreased across adolescence to negligible amounts in late adolescence. Findings are commensurate with the deliberate practice framework and early engagement.